Polarisasi Politik di Indonesia 2014-2019: Sebuah Kajian Pustaka - Mansyur, Ibnu Chaerul (JPP (Jurnal Politik Profetik), 2023)
In the 1950s, political life was divided due to sect politics. The New Order and Reform had suppressed and made political polarization subside, but political polarization strengthened again in 2014, due to the meeting of two spectrums between pluralist and Islamist groups. This study aims to examine the causes of the strengthening of political polarization between Islamists and pluralists in Indonesia, after it has faded for so long in a repressive and open political system. This research uses a qualitative approach with literature study method. The results of the study found that political actors pursue their political goals by using polarization strategies, such as mobilizing voters to divide them, spreading hate speech, and exploiting public unrest. The conclusion is that the political polarization that occurred between Islamists and pluralists in Indonesia in 2014-2019 was caused by strategic political actors. This research will add to the study of political polarization in Indonesia which is still limited, especially those discussing the causes of political polarization.